FAKTOR - FAKTOR YANG MEMPENGARUHI PROFITABILITY PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Novieany, Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2020)
The purpose of this thesis is to examine the effect of leverage, sales growth, firm size and working capital management on profitability in manufacturing companies listed on the Indonesia  Stock  Exchange.  The  sample  selection  technique  in  this  study  used  a  purposive sampling technique with a total sample of 27 manufacturing companies in the period 2015-2017. The data used in this study is secondary data which is processed using the program Eviews 9.0. The results of this study indicate that the size of the company has a negative influence on profitability while leverage, sales growth, and working capital management have no effect on profitability.